Measurement and modelling of diffusion coefficients of ketones in ethanol - Faria, Sofia Neto (2024)
The interest in supercritical fluid extraction (SFE) to obtain bioactive compounds has risen over the years. This interest derives from a lower environmental impact of supercritical fluids (SFC), compared to the conventional solvents, and due to the quality and purity of the final products, which in turn, leads to the need of knowledge about the compounds transport properties for the accurate design of industrial processes. The initial objective of this dissertation was the measurement and modelling of binary diffusion coefficients (12) of bioactive compounds in supercritical mixtures of CO2 (SC-CO2) and ethanol. However, due to problems in the experimental installation, it was not possible to operate with SC-CO2 so 12 was measured in ethanol. These data will be important for modelling the properties of CO2 and ethanol mixtures. The 12 of five ketones (acetone, 2-butanone, 2-pentanone, 2-hexanone and 3-hexanone) were measured in ethanol, in the range of 1 − 150 and 303.15 −333.15 , using the Chromatographic Peak Broadening (CPB) method. The obtained results were in the range of [1.77− 2.89]∙ 10−5 (2 −1 ) for acetone, [1.53 − 2.63]∙ 10−5 (2 −1 ) for 2-butanone, [1.39 − 2.41]∙ 10−5 (2 −1 ) for 2-pentanone, [1.29 − 2.18]∙ 10−5 (2 −1 ) for 2-hexanone and [1.28 − 2.17]∙ 10−5 (2 −1 ) for 3-hexanone. Experimental data were analysed using models based on the free volume theory (e.g. Dymond-Hildebrand-Batschinski, DHB), on the hydrodynamic theory, hybrid models (e.g. Tracer Liu-Silva-Macedo, TLSM) and empirical correlations. The models were assessed in terms of the mean absolute relative deviation (). The most suitable models to represent 12 were: DHB for acetone, 2-butanone, 2-pentanone, 2- hexanone and 3-hexanone ( = 2.22 %, 2.43 %, 2.37 %, 2.33 % and 3.65 %, respectively), TLSMd for acetone, 2-butanone, 2-pentanone, 2-hexanone and 3-hexanone ( = 0.90 %, 1.82 %, 1.91 %, 1.56 % and 2.63 %, respectively) and Magalhães et al. correlation for acetone, 2-butanone, 2-pentanone, 2-hexanone and 3-hexanone ( = 0.42 %, 0.89 %, 0.45 %, 0.49 % and 1.13 %, respectively).